Nipple adenoma in a 2‐year‐old boy. Issue 3 (26th February 2018) - Fujisawa, Kou; Kato, Motoi; Kono, Tatsuki; Utsunomiya, Hiroki; Watanabe, Azusa; Watanabe, Shoji
Abstract: Nipple adenoma is an uncommon proliferative process of the breast and predominantly occurs in women aged 40‐50. Its incidence is extremely low in men, and it has not been reported in a boy. Although nipple adenoma is rare and benign, being familiar with it is important because it clinically resembles Paget disease and histologically adenocarcinoma. We report a case of nipple adenoma in a boy.